Remarques sur les fonctions érudites et méditatives de l’eschatologie dans le haut Moyen Âge ibérique - Gaelle Bosseman (Bulletin du Centre d’Études Médiévales d’Auxerre)
Taking a stance in the historiographical debate on the reality of millenarian fears at the approach of the year 800 and the year 1000, this article offers a reinterpretation of some texts on the end of times in the Iberian Peninsula in the Early Middle Ages. By observing their composition and their context of transmission, the objective is to show that these texts have assumed erudite and scholarly functions – compilation of knowledge, inculcation of eschatological doctrine, teaching, etc. – a priori detached from any fearful expectation of the last days. Object of knowledge as much as of belief, eschatology is mainly approached by medieval scholars through the exegesis of prophecies ; the study furthermore endeavors to restore the spiritual and meditative dimension in which the texts on the end of times were read and studied.